Ankle Arthrodesis with Cannulated Screw: Case Series - Andre Triadi Desnantyo; Muhammad Zaim Chilmi; Hizbillah Yazid (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACT Ankle osteoarthritis patients are young and lack of available long last treatment. Ankle arthrodesis remains the gold standard and is the procedure of choice for younger patients who are heavy laborers. These case series evaluate and report five patients undergone ankle arthrodesis at RSUD Dr. Soetomo Surabaya on 2012-2016. The data were collected from patient files, radiographs, and a recent physical examination. The outcome has been assessed with SF-36 score and clinical scoring system Ankle-Hind foot American Foot and Ankle Society. Three male patients and two female patients underwent ankle arthrodesis with cannulated screw, caused by neglected severe ankle dislocation. One patient had open dislocation. Based on SF-36 scoring, the five patients had average score 76,7 with highest and lowest score were 95,9 and 56,7. Based on clinical score ankle-hind foot American Ankle and Foot Society, the average score was 68(51 – 88). The scoring result includes general health, physic, emotional, and social. And clinical scoring ankle-hind foot American Foot and Ankle Society evaluation includes pain, function, and alignment. It shows that there was patient that gains an almost perfect result. Patient with the lowest score also had knee osteoarthritis contralateral from the operated ankle. Early weight bearing on ankle arthrodesis with cannulated screw was the major factor caused unsatisfactory result of this patient. Ankle arthrodesis with cannulated screw has satisfactory result eventhough remain complain on one patient. Nevertheless, ankle arthrodesis with cannulated screw still has an important role in the treatment of choice on ankle reconstruction.Keywords                   : Ankle arthrodesis, cannulated screw, ankle joint fusion